Ultrasound guidance versus landmark method for peripheral venous cannulation in adults - Tada, Masafumi (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness and safety of the ultrasound‐guided method compared with the landmark method for peripheral intravenous cannulation in adults.